2010
DOI: 10.2500/aap.2010.31.3396
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of multidisciplinary resources for vaccination of egg-allergic individuals during an H1N1 (novel) influenza pandemic

Abstract: Egg allergy is a contraindication for influenza vaccination because of the presence of trace egg protein. Although recent reports suggest that egg-allergic individuals can be safely immunized with seasonal influenza vaccine, the safety of H1N1 influenza vaccine in this context has not previously been reported. This study was designed to investigate how to safely immunize high-risk populations during the H1N1 influenza pandemic for whom the vaccine would be contraindicated. Vaccination of egg-allergic children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Less severe reactions not described as anaphylaxis but involving cardiovascular symptoms, respiratory symptoms, angioedema, or generalized urticaria, or which involved treatment with medications or outpatient or emergency department attention occurred with low frequency (<1%). A similar profile was noted among 13 studies of monovalent H1N1pdm09 influenza vaccine, with no reported instances of anaphylaxis; frequency of reactions involving cardiovascular symptoms, respiratory symptoms, angioedema, or generalized urticaria events of <1%, and of events involving treatment with medications or outpatient or emergency department attention of approximately 1.5% (certainty level: very low) (114,115,(123)(124)(125)(126)(127)(128)(129)(130)(131)(132). One US Department of Health and Human Services/Centers for Disease Control and Prevention instance of anaphylaxis meeting a surveillance case definition (i.e., Brighton Level 1 criteria) in a person with possible egg allergy was noted in a summary of VAERS reports after administration of monovalent H1N1pdm09 influenza vaccine during the 2009-10 influenza season; no denominator of doses administered was available but it was noted that approximately 127 million doses of monovalent IIV were distributed in the United States that season (133).…”
Section: Persons With a History Of Egg Allergysupporting
confidence: 64%
“…Less severe reactions not described as anaphylaxis but involving cardiovascular symptoms, respiratory symptoms, angioedema, or generalized urticaria, or which involved treatment with medications or outpatient or emergency department attention occurred with low frequency (<1%). A similar profile was noted among 13 studies of monovalent H1N1pdm09 influenza vaccine, with no reported instances of anaphylaxis; frequency of reactions involving cardiovascular symptoms, respiratory symptoms, angioedema, or generalized urticaria events of <1%, and of events involving treatment with medications or outpatient or emergency department attention of approximately 1.5% (certainty level: very low) (114,115,(123)(124)(125)(126)(127)(128)(129)(130)(131)(132). One US Department of Health and Human Services/Centers for Disease Control and Prevention instance of anaphylaxis meeting a surveillance case definition (i.e., Brighton Level 1 criteria) in a person with possible egg allergy was noted in a summary of VAERS reports after administration of monovalent H1N1pdm09 influenza vaccine during the 2009-10 influenza season; no denominator of doses administered was available but it was noted that approximately 127 million doses of monovalent IIV were distributed in the United States that season (133).…”
Section: Persons With a History Of Egg Allergysupporting
confidence: 64%
“…Although this is a small number of patients relative to the overall study population, more patients may be referred for this vaccine in the future as a national programme has been rolled out. Allergic reaction to this vaccine is uncommon, however (23).…”
Section: Discussionmentioning
confidence: 99%
“…These allergic reactions rates did not differ significantly from those in non‐egg‐allergic controls [24‐26]. In investigations published in the last ten years [21,23‐37] the frequency of allergic reactions to vaccine was 2.62% in 6532 subjects (Table 1). The American Academy of Paediatrics [19] has recently stated that the risks of missing influenza vaccination outweigh those from vaccination itself.…”
Section: Reviewmentioning
confidence: 73%